Gut microbiota, circulating metabolites, and gallstone disease: a Mendelian randomization study - Hu, Xutao; Binxu, Qiu; Shao, Guang-zhao; Huang, Yu; Qiu, Wei (Frontiers in Microbiology, 2024)
Background The link between Gut microbiota (GM) and Gallstone disease (GSD) is well established, but it is not clear whether there is a causal relationship between the two associations. Methods We conducted bidirectional Mendelian randomization (MR) analyses, leveraging aggregated data from the Genome-Wide Association Study (GWAS) of GM and Circulating Metabolites. Our primary objective was to investigate the causal interplay between intestinal flora and GSD. Additionally, we performed mediational analyses, two-step MR, and multivariate MR to uncover the potential mediating effect of circulating metabolites in this relationship. Result Our study has revealed a causal relationship between GSD and six distinct bacterial groups. Genetically predicted Class Bacilli (Odds Ratio (OR): 0.901, 95% Confidence Interval (95% CI): 0.825–0.985; p = 0.021), Order Lactobacillales (OR: 0.895, 95% CI: 0.816–0.981; p = 0.017), and Genus Coprococcus 2 (OR: 0.884, 95% CI: 0.804–0.973; p = 0.011) were inversely associated with the risk of GSD. Conversely, the Genus Clostridiumsensustricto1 (OR: 1.158, 95% CI: 1.029–1.303; p = 0.015), Genus Coprococcus3 (OR: 1.166, 95% CI: 1.024–1.327; p = 0.020), and Genus Peptococcus (OR: 1.070, 95% CI: 1.017–1.125; p = 0.009) were positively associated with the risk of GSD. Moreover, our findings suggest that the positive influence of the Genus Peptococcus on GSD may be mediated through Omega-3 polyunsaturated fatty acids (PUFA). Conclusion This study reinforces the connection between the gut microbiome and the risk of GSD while also unveiling the mediating role of Omega-3 PUFA in the causal relationship between these factors.